Đáp án: Giải thích các bước giải: x³ – x² – 21x + 45 = x³ + 5x² – 6x² – 30x + 9x+ 45 =( x³ + 5x²)-( 6x² + 30x ) + (9x+ 45) = x²( x + 5) – 6x ( x +5) + 9( x +5) = ( x + 5)( x² – 6x +9) = ( x +5)( x² – 2.3x + 3² ) = ( x +5)( x – 3)² Chúc bn hok tốt ! Bình luận
Đáp án: CHÚC BẠN HỌC TỐT !!!!!!!!! Giải thích các bước giải: $x³ – x² – 21x + 45$ $= x³ – 3x² + 2x² – 6x – 15x + 45$ $= (x³ – 3x²) + (2x² – 6x) – (15x – 45)$ $= (x – 3).(x² + 2x – 15)$ $= (x – 3).[(x² – 3x) + (5x – 15)]$ $= (x – 3).(x – 3).(x + 5)$ $= (x – 3)².(x + 5)$ Bình luận
Đáp án:
Giải thích các bước giải:
x³ – x² – 21x + 45
= x³ + 5x² – 6x² – 30x + 9x+ 45
=( x³ + 5x²)-( 6x² + 30x ) + (9x+ 45)
= x²( x + 5) – 6x ( x +5) + 9( x +5)
= ( x + 5)( x² – 6x +9)
= ( x +5)( x² – 2.3x + 3² )
= ( x +5)( x – 3)²
Chúc bn hok tốt !
Đáp án:
CHÚC BẠN HỌC TỐT !!!!!!!!!
Giải thích các bước giải:
$x³ – x² – 21x + 45$
$= x³ – 3x² + 2x² – 6x – 15x + 45$
$= (x³ – 3x²) + (2x² – 6x) – (15x – 45)$
$= (x – 3).(x² + 2x – 15)$
$= (x – 3).[(x² – 3x) + (5x – 15)]$
$= (x – 3).(x – 3).(x + 5)$
$= (x – 3)².(x + 5)$